Transcriptome Sequencing of Agave amaniensis Reveals Shoot-Related Expression Patterns of Expansin A Genes in Agave - Xuxia Wang; Xing Huang; Lisha Chen; Zhouli Xie; Shibei Tan; Xu Qin; Tao Chen; Yanlei Huang; Jingen Xi; Helong Chen; Kexian Yi (Plants, 2023)
Agave species are widely planted for fiber production. However, the molecular basis of agave fiber development has not been well understood. In this study, we performed a transcriptomic analysis in A. amaniensi, a well-known variety with high-quality fiber production. Approximately 43.87 million clean reads were obtained using Illumina sequencing. The de novo assembly produced 66,746 unigrams, 54% of which were annotated in a public database. In the Nr database, 21,490 unigenes of A. amaniensis were shown to be most closely related to Asparagus officinalis. Nine expansin A orthologs with full coding regions were obtained, which were named EXP1a, EXP1b, EXP2, EXP3, EXP4a, EXP4b, EXP11, EXP12, and EXP13. The maximum likelihood phylogenetic tree revealed the species-specific expansion of expansin genes in Arabidopsis, rice and agave. The expression analysis suggested the negative correlation between the expression of expansin genes and the leaf growth rate, except AhEXP11. Moreover, expansin genes were differentially affected by abiotic and biotic stresses. Notably, AhEXP2 expression level was highly upgraded after the infection of Phytophthora nicotiana. Nutrient deficiency also influent expansin genes expression. Together, our research will benefit future studies related to fiber development, disease resistance and nutrient usage in agave.